Genetic diversity analysis of three Indian sheep breeds using microsatellite markers - R Arora; S Bhatia (Journal of Livestock Biodiversity, 2025)
Information is presented on the genetic diversity analysis involving within breed variability, genetic differentiation and genetic relationships among Jalauni, Marwari and Sonadi sheep breeds of Northwestern arid and semi arid zone of India, based on twenty microsatellite markers as proposed in FAO’s MODAD programme. The considerably high values obtained for allele and gene diversity showed that Jalauni, Marwari and Sonadi breeds possessed considerable amount of genetic diversity. A difference in inbreeding was elucidated by within population inbreeding estimate (F, ), with Marwari exhibiting comparatively high level of inbreeding than Jalauni and Sonadi breeds. The present study thus elucidated the need for concerted genetic management efforts to be taken to combat harmful/adverse effects of inbreeding in the investigated breeds especially Marwari. The three investigated breeds also reflected absence of a recent genetic bottleneck. The pair wise genetic distance (DS), genetic differentiation (F), gene differentiation (GT) and gene flow (Nm) between Jalauni, Marwari and Sonadi revealed Marwari and Sonadi to be the closest and highest degree of genetic differentiation was found between Jalauni and Sonadi. In addition, phylogeny analysis used to evaluate inter-breed genetic proximity also revealed substantial genetic differentiation between Jalauni and the other two sheep breeds of Northwestern arid and semi arid zone of India (Marwari and Sonadi). The generated molecular genetic information of breeds under consideration would provide a more precise insight for their conservation, genetic management and genetic improvement programmes.